The Gut-Kidney Axis: Putative Interconnections Between Gastrointestinal and Renal Disorders - Lehto, Markku; Groop, Per-Henrik (Frontiers in Endocrinology, 2018)
Diabetic kidney disease (DKD) is a devastating condition associated with increased morbidity and premature mortality. The etiology of DKD is still largely unknown. However, the risk of DKD development and progression is most likely modulated by a combination of genetic and environmental factors. Patients with autoimmune diseases, like type 1 diabetes, inflammatory bowel disease, and celiac disease, share some genetic background. Furthermore, gastrointestinal disorders are associated with an increased risk of kidney disease, although the true mechanisms have still to be elucidated. Therefore, the principal aim of this review is to evaluate the impact of disturbances in the gastrointestinal tract on the development of renal disorders.